Evaluating the Level of Clinical Communication Skills in Dental Students at Guilan University of Medical Sciences - Narges Simdar; Rasoul Tabari-Khomeiran; ashkan Salari; Kaveh karim; Ensie Teimoori (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: The ability to communicate correctly is one of the basic skills of social life. Considering the importance of communication skills between dentists and patients and the lack of this study among dental students in Iran, this study aimed to determine the level of clinical communication skills in the last three years of dental students at Guilan University of Medical Sciences, Rasht, Iran. Methods: In this cross-sectional analytical study, students responded to the Persian version of the validated Dental Consultation Communication Checklist (DCCC), the validity and reliability of which have been confirmed. This questionnaire consists of five domains, four of which are related to the student, namely introduction (5 questions), history (12 questions), examination (8 questions), conclusion (3 questions), and one domain is related to the patient (3 questions). The scores are rate using a Likert scale. Accordingly, scores 1 and 7 indicate lowest and highest levels of self-expression, respectively. Data were analyzed using IBM SPSS (version 22.0), and level of significance was set at 0.05. Results: In total, 106 students, including 40 males and 66 females, with a mean age of 25.7±3.3 years, participated in the study. The mean scores of the subjects in the introduction, history, and examination domains were 19.6±3.1, 45±7.0, and 31.8±4.4, respectively. Moreover, in the last two domains (i.e., conclusion and patient) the scores were obtained at 11.9±2.3 and 12.3±2.7, respectively. The mean total score was determined at 120.6±9.7. Moreover,between five different domains and the total score of the questionnaire showed no significant relationship with age, gender, marital status, and academic year. Conclusion: Some dimensions of communication skills in students such as introducing,history,examination and conclusion of  the sessions must be improved. Considering the important role of communication skills in effective interaction with patients, designing and performing Interventional training and practical workshops are necessary to improve communication skills among dental students.